Development and Exploitation of KASP Assays for Genes Underpinning Drought Tolerance Among Wheat Cultivars From Pakistan - Ur Rehman, Shoaib; Ali Sher, Muhammad; Saddique, Muhammad Abu Bakar; Ali, Zulfiqar; Khan, Mahmood Alam; Mao, Xinguo; Irshad, Ahsan; Sajjad, Muhammad; Ikram, Rao Muhammad; Naeem, Mahnoor; Jing, Ruilian (Frontiers in Genetics, 2021)
Abstract High throughput genotyping for functional markers offers an excellent opportunity to effectively practice marker assisted selection while breeding cultivars. We developed kompetitive allele specific PCR (KASP) assays for genes conferring drought tolerance in common wheat (Triticum aestivum L.). In total, 11 KASP assays, developed in this study and five already reported assays were used for their application in wheat breeding. We investigated alleles at 16 loci associated with drought tolerance among 153 Pakistani hexaploid wheat cultivars released during 1953-2016, twenty-eight diploid wheat accessions (16 for AA and 12 for BB), and 19 tetraploid wheat (AABB) were used to study the evolutionary history of the studied genes. Superior allelic variations of the studied genes were significantly associated with higher grain yiled. Favored haplotypes of TaSnRK2.3-1A, TaSnRK2.3-1B, TaSnRK2.9-5A, TaSAP-7B, and TaLTPs-1A, predominated in Pakistani wheat germplasm indicating unconscious pyramiding and selection pressure on favorable haplotypes during selection breeding. TaSnRK2.8-5A, TaDreb-B1, 1-feh w3, TaPPH-7A, and TaMOC-7A, TaPARG-2A had moderate to low frequencies of favorable haplotype among Pakistani wheat germplasm pointing towards introgression of favorable haplotypes by deploying functional markers in marker assisted breeding. The KASP assays were compared with gel-based markers for reliability and phenotypicaaly validated among sixty-two Pakistani wheat cultivars. Association analyses showed that the favroable allelic variations were significantly associated with grain yield contributing traits. The developed molecular marker toolkit of the genes, can be instrumental for the wheat breeding in Pakistan.